EFFECT OF MIDAZOLAM PREMEDICATION ON DOSES OF PROPOFOL FOR LARYNGEAL MASK AIRWAY INSERTION IN CHILDREN - Adnan, Muhammad; Furqan, Aamir; Sattar, Muhammad Kaleem (Journal of Ayub Medical College Abbottabad, 2017)
Background: Propofol is a widely-accepted medication for the successful insertion of laryngeal mask airway (LMA). When propofol is used alone, larger doses are required which can lead to cardiorespiratory distress resulting in hypotension and prolonged apnoea. The objective of this study was to evaluate the effect of premedication of midazolam on different doses of propofol for LMA insertion. Methods: In this randomized clinical trial, eighty-six (86) patients who were scheduled to undergo elective surgery is supine position not requiring the need for tracheal intubation from September 2015 to 6 March 2016 were included. In group I (n=43), the LMA was introduced after induction of anaesthesia with Propofol alone. In Group II (n=43, the patient was premeditated with midazolam (0.05 mg/kg) before induction of anaesthesia with propofol. Each group was divided into three subgroups depending upon the dose of propofol used for LMA insertion. Results: In this study, there were 53.5% females in group I and 48.8% females in group II. The mean age of Children in group I was 7.30±2.55 years and 7.47±2.46 years in group II. Incidence of incomplete Jaw relaxation, coughing and limb movements was significantly high in in Group I patients (p-values <0.001, <0.001 and <0.001 respectively). Effectiveness of anaesthesia was compared among different subgroups. On comparison of subgroup Ia and IIa, the effectiveness rate was significantly high in subgroup IIa 50% versus only 7.1% in subgroup Ia (p-value 0.012). Similarly, in subgroup IIb effectiveness was achieved in 100% patients as compared to only 64.3% patients in subgroup IIb (p-value 0.014). There was no significant difference in effectiveness rate in subgroup Ic and IIc (p-value 0.309). Conclusion: With midazolam pre-medication, the dose of propofol for LMA insertion is decreased. The incidence of adverse events during LMA insertion is also low with midazolam premedication. Keywords: Laryngeal mask airway; Propofol; Midazolam